Poxviral-based vaccine elicits immunologic responses in prostate cancer patients - Madan, Ravi A (Landes Bioscience, 2014)
Prostvac is a poxviral-based vaccine designed to target prostate-specific antigen (PSA) in prostate cancer patients. Recently, the potential toxicity and immunological impact of this immunotherapy were reviewed in the context of new clinical data. Our findings suggest that Prostvac is safe and elicits anticancer immune responses, both alone and in combinatorial approaches.